HEALTH EDUCATION ON PREVENTING AND MANAGING HYPERTENSION IN CIHANJUANG RAHAYU VILLAGE - Tambunan, Evelyn Hemme; Haro, Masta (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Hypertension is known as the "silent killer" and remains one of the leading causes of morbidity and mortality globally. In Indonesia, the prevalence of hypertension is still high, particularly in rural areas where access to accurate health information is often limited. This Community Service Program (Pengabdian kepada Masyarakat, or PkM) aimed to improve community health literacy and self-management skills related to hypertension prevention and control among residents of Cihanjuang Rahayu Village, West Bandung Regency. The PkM activities included basic health screening, interactive health education sessions (lectures, discussions, and demonstrations), and evaluation using a quasi-experimental design with pre-test and post-test questionnaires on knowledge and behaviour. A total of approximately 35 participants were involved, consisting of older adults, health cadres, and individuals at risk for hypertension. The findings indicated a significant increase (p < .05) in participants’ knowledge scores, from a pre-test mean of 64.5 to a post-test mean of 89.2. The greatest improvement was observed in understanding lifestyle modification, especially the importance of a low-salt diet and medication adherence. The program successfully empowered the community by enhancing knowledge and awareness about hypertension prevention and management. Increased health literacy is expected to contribute to long-term behavioural change, supporting early detection and sustainable control of hypertension at the community level.